H. H. Hacker Moths of Africa. Systematic and Illustrated Catalogue of the Heterocera of Africa. Volume 2. Rivulinae, Hypeninae, Herminiinae, Hypenodinae (Erebidae) - A. Vives Moreno (SHILAP, 2021)
Revisión de Publicaciones